Kajian Tingkat Penerapan Manajemen Mutu pada UMKM Pengolah Ikan Pindang Tradisional dan Higienis di Kabupaten Bogor - Bremanti, Lisa; Hubeis, Musa; Palupi, Nurheni Sri (Institut Pertanian Bogor, 2018)
Boiled fish is a processing of fishery products that have great potential because of high public demanding. UMKM Cindy Group is a small and medium enterprise in Bogor regency who wished that their product could be competitive, so that the application of quality management is required. The objectives of this research were: (1) to identify the level of quality management implementation at traditional and hygienic boiled fish SMEs as well as; (2) to analyze the relation of the level of quality application to the performance of traditional and hygienic boiled fish SMEs. The method used was descriptive analysis; trend analysis (financial performance: Net Profit Margin (NPM), Return on Investment (ROI), Return on Equity (ROE) and non-financial performance (number of training, production volume, number of customers); and discriminant analysis. Sampling technique for filling questionnaire was purposive sampling. The results of the study found that the level of application of quality management system at traditional boiled fish was at the level between Quality Control Operator (OQC) and Foreman Quality Control (FQC), while hygienic cleansing was at the level between Statistic Quality Control (SQC) and Total Quality Management (TQM). The result of discriminant analysis show that the level of SMM implementation has an effect on the company performance of UD Cindy Group that was seen from sig value <0.05. On hygienic displacement had an increasing trend of non-financial performance and higher on the average of the last three years compared with traditional boiled fish